A new Mexican species of Onthophagus Latreille (Coleoptera: Scarabaeidae: Scarabaeinae), with a revised key to the species of the O. dicranius species complex - Delgado, Leonardo; Mora-Aguilar, Eder F. (Zootaxa, 2019)
New World species of the genus Onthophagus Latreille (Coleoptera: Scarabaeidae: Scarabaeinae) have been classified in different ways, all of them without a phylogenetic framework. For instance, Boucomont (1932) separated them in 13 groups of species, but Zunino & Halffter (1988; 1997) only recognize five species groups. Howden & Gill (1993) add the O. dicranius Bates and O. mirabilis Bates species groups, and Kohlmann & Solís (2001) added the O. gazellinus Bates species group. Also, over the years, groups, complexes, and sets of species have been defined using different criteria not even comparable each other. Two of these groupings are the O. dicranius and O. mirabilis species groups, which were firstly separated from the O. clypeatus Blanchard species group (sensu Zunino & Halffter 1981, 1997) by Howden & Gill (1993). After, Kohlmann & Solís (2001) later merged both groups under the O. dicranius species group. Finally, Génier (2017) gives a conceptual framework for species groups and complexes, thus assigning the status of species complex to the two previous species groups, and integrating them in the O. dicranius species group. Herein, we describe a new species of the O. dicranius species complex, update the species list of this complex, and present a revised key to separate these species.